RESPON BEBERAPA VARIETAS KEDELAI (Glycine max (L) Merril) TERHADAP PEMBERIAN GIBERELIN - Panca Putra S; Aslim Rasyad; Nurbaiti ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Plant growth regulator such as gibberellins () is considered as a crucial part in soybean cultural practices; however, the information on its beneficial has been limited. So, this experiment  was intended to look at the impact of on soybean growth and yield components and the response of different varieties on . A field experiment was arranged in a split plot design, in which three levels of concentration as main plot and three cultivars as sub plot. Gibberellins applied were 125 ppm, 250 ppm, and control. The cultivars used were Kaba, Wilis, and Anjasmoro. Seed of soybean cultivars was planted in a plot of 3.2 m by 3 m with planting space 40 cm by 15 cm. At 21 days after planting, was sprayed to the plants according to treatments in which spraying rate of 384 ml every plot. Parameters observed were crop growth rate, internodes length, days to flowering, filled pod numbers per plant, seed numbers per plant, grain yield per m2, harvest index, and 100-seed weight. The results showed that application of gibberellin significantly lengthened main stem internodes,  increased grain yield but decreased  plant growth rate, and 100-seed weight. This results indicate that  application of should be used carefully in soybean cultural practice. Keywords: gibberellin, soybean varieties, growth rate, grain yield, harvest index